God and the founders : Madison, Washington, and Jefferson - Muñoz, Vincent Phillip (Cambridge University Press, 2009)
"By analyzing Madison's, Washington's, and Jefferson's public documents, private writings, and political actions, Muñoz explains the founders' competing church-state political philosophies."--Page i